2020
DOI: 10.1186/s12937-020-00605-0
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Effectiveness of gender-targeted versus gender-neutral interventions aimed at improving dietary intake, physical activity and/or overweight/obesity in young adults (aged 17–35 years): a systematic review and meta-analysis

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
2
0
1
Order By: Relevance
“…A closer look at our dietary outcomes as measured by self-reported fruit and vegetable intake shows that our mean increase of .8 serving per day (an increase of 24% from baseline), compares favorably with overall outcomes of increases between .1–1.4 servings per day (or a 9.7% to 59.3% increase from baseline) reported in reviews of lifestyle interventions designed to increase adult fruit and vegetable intake. 30 - 33 If maintained, our reported increase in nuts intake is similar in magnitude to that observed in the PREDIMED trial’s nut arm where increased nut intake was associated with a 28% reduction in CVD events. 34 General improvements in healthy eating pattern by increased fruit and vegetable intake also contribute to systolic blood pressure reductions, 35 which in turn are associated with risk reductions for major cardiovascular events and all-cause mortality.…”
Section: Discussionsupporting
confidence: 77%
“…A closer look at our dietary outcomes as measured by self-reported fruit and vegetable intake shows that our mean increase of .8 serving per day (an increase of 24% from baseline), compares favorably with overall outcomes of increases between .1–1.4 servings per day (or a 9.7% to 59.3% increase from baseline) reported in reviews of lifestyle interventions designed to increase adult fruit and vegetable intake. 30 - 33 If maintained, our reported increase in nuts intake is similar in magnitude to that observed in the PREDIMED trial’s nut arm where increased nut intake was associated with a 28% reduction in CVD events. 34 General improvements in healthy eating pattern by increased fruit and vegetable intake also contribute to systolic blood pressure reductions, 35 which in turn are associated with risk reductions for major cardiovascular events and all-cause mortality.…”
Section: Discussionsupporting
confidence: 77%
“…Prior studies have indicated gender differences in eating behavior, as well as the psychological factors associated with weight gain and maintenance, highlighting the need for gender-targeted weight loss interventions [ 29 , 40 ]. As the effectiveness of gender dichotomous tailoring does not significantly differ from that of gender-neutral interventions [ 45 ], we implemented gender-sensitive self-tailoring features. The participants could choose between 2 gender-targeted versions at the beginning of the modules.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of reviewed studies, investigating the effect of gender on overweight and obesity outcomes to improve the effectiveness of WLPs is an important research agenda. A recently published meta-analysis comparing the effects of gender-targeted and gender-neutral WLPs however revealed no differences in weight-related outcomes, although gender-targeted interventions were more effective in promoting activity and improving nutrition [ 45 ]. However, the included gender-targeted WLPs were offered either to male or to female participants based on sex.…”
Section: Introductionmentioning
confidence: 99%
“…En el caso particular de los adolescentes y adultos jóvenes entre los 17-21 años de edad, resulta particularmente relevante por múltiples razones, la primera de ellas, es la edad en la que se encuentran. Durante esta etapa de desarrollo los adolescentes están en un proceso de transición entre la infancia y la vida adulta, lo que implica cambios no sólo emocionales, sino actitudinales y de comportamientos que determinarán muchos de sus hábitos de salud durante su vida adulta (Sharkey et al, 2020).…”
Section: El Estigma Del Pesounclassified